The Abdication of the Israeli Pound as a Standard of Measurement for Medium and Long-Term Contracts - Rubner, A. (Review of Economic Studies, 1960)
Journal Article The Abdication of the Israeli Pound as a Standard of Measurement for medium and long-term Contracts Get access A. Rubner A. Rubner Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 1, October 1960, Pages 69–75, https://doi.org/10.2307/2296252 Published: 01 October 1960